15.6k views
1 vote
Given: f(x) = x² and g(x) = 2x + 1, find f[g(x)].

2 Answers

3 votes

Answer:

4x² + 4x + 1

Explanation:

To obtain f(g(x)), substitute x = g(x) into f(x)

f(g(x)) = f(2x + 1) = (2x + 1)² = 4x² + 4x + 1

User Zliw
by
8.1k points
4 votes

For this case we have by definition that:


(f_ {0} g) (x) = f [g (x)]

They tell us that:


f (x) = x ^ 2\\g (x) = 2x + 1

So:


(f_ {0} g) (x) = f [2x + 1] = (2x + 1) ^ 2 = (2x) ^ 2 + 2 (2x) (1) + 1 ^ 2 = 4x ^ 2 + 4x + 1

ANswer:


f [g (x)] = 4x ^ 2 + 4x + 1

User Gabriel Ferrarini
by
6.7k points